2014
DOI: 10.1017/s0266462314000051
|View full text |Cite
|
Sign up to set email alerts
|

Risks in the Implementation and Use of Smart Pumps in a Pediatric Intensive Care Unit: Application of the Failure Mode and Effects Analysis

Abstract: Carrying out an FMEA made it possible to detect risk points in the use of smart pumps, take action to improve the tool, and adapt it to the PICU. Providing user training and support tools and continuously monitoring results helped to improve the usefulness of the drug library, increased users' compliance with the drug library, and decreased the number of unnecessary alarms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 28 publications
0
35
0
1
Order By: Relevance
“…In infusion pumps, nuisance alarms can take the form of frequent air-in-line alarms as a result of microbubbles; occlusion alarms as a result of kinked administration sets or positional intravenous catheters; hold, expired, or inactivity alarms; and battery alarms. Evidence suggests that increased training and education can help reduce the number of nuisance alarms 3,7,21,27. In a study involving a pediatric ICU, Manrique-Rodríguez et al27 found that providing user training and support tools, as well as continuously monitoring results, decreased the number of unnecessary pump alarms and that alarms that sounded were taken more seriously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In infusion pumps, nuisance alarms can take the form of frequent air-in-line alarms as a result of microbubbles; occlusion alarms as a result of kinked administration sets or positional intravenous catheters; hold, expired, or inactivity alarms; and battery alarms. Evidence suggests that increased training and education can help reduce the number of nuisance alarms 3,7,21,27. In a study involving a pediatric ICU, Manrique-Rodríguez et al27 found that providing user training and support tools, as well as continuously monitoring results, decreased the number of unnecessary pump alarms and that alarms that sounded were taken more seriously.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that increased training and education can help reduce the number of nuisance alarms 3,7,21,27. In a study involving a pediatric ICU, Manrique-Rodríguez et al27 found that providing user training and support tools, as well as continuously monitoring results, decreased the number of unnecessary pump alarms and that alarms that sounded were taken more seriously. Kurnat-Thoma and Shah3 characterized pump alarms and associated nurse perceptions across 6 care units, concluding that there was a need to improve staff education specific to clustering tasks around medical device alarms.…”
Section: Discussionmentioning
confidence: 99%
“…In the pediatric context, implementing new IP smartpumps, when assessed through analysis of modes and failures, several points of risk during the implementation and use process were also found by its users (25) . However, improvements were suggested through the role of the staff itself, such as introducing capital letters to help users differentiate names of similar drugs, promoting more safety in the use of equipment and improvements in care practice.…”
Section: Resultsmentioning
confidence: 99%
“…15,16 It has also been considered an excellent tool for the evaluation of patient safety after the implementation of information technologies (ITs) like computerized physician order entry (CPOE) and smart pumps. 17,18 However, given the scant evidence about the reliability and validity of FMECA, 19 it would not be appropriate to recommend its use alone as a tool for preventing patient harm. To overcome this limitation, we combined risk analysis using FMECA methodology with the objective measures of a traditional cross-sectional medication error rate study.…”
Section: Introductionmentioning
confidence: 99%